Revisão integrativa do uso de medicamentos corticosteroides para o tratamento dos sintomas do Transtorno do Espectro do Autismo - Jesus, Lillian Amanda Gabarrão de (2024)
Autism Spectrum Disorder (ASD) is a neurodevelopmental pathology characterized by persistent impairments in both communication and social interaction, coupled with the presence of restricted and repetitive patterns of behavior, interests, or activities. Corticosteroids have been used to treat symptoms associated with ASD. We conducted a systematic review of study investigating the clinical effects of corticosteroids use in relation to their efficacy, safety, and adverse effects in the treatment of ASD. The search was performed across four databases: PubMed, Scopus, Web of Science e Google Acadêmico. Nine studies were selected and analyzed, they presented a minimal risk of bias, and eight studies were composed of children and adolescents with ASD and one in an animal model. Thus, the articles proved that the use of corticosteroids safely reduced the symptoms of ASD, including hyperactivity and irritability. Furthermore, an improvement in stereotypical and social behaviors was shown, thus treating the core symptoms of ASD and without serious adverse effects. Treatment with corticosteroids may hold promising effects in managing central symptoms and those associated with ASD, either used alone or in combination with other medications or even non pharmacological therapie